Hydrocracking of α-Cellulose Using Co, Ni, and Pd Supported on Mordenite Catalysts - Wega Trisunaryanti; Triyono Triyono; Ria Armunanto; Lathifah Puji Hastuti; Desinta Dwi Ristiana; Resi Vita Ginting (Universitas Gadjah Mada, 2018)
Hydrocracking of α-cellulose has been conducted in a semi-batch reactor at 400, 450, and 500 °C with hydrogen flow (30 mL/min.) for 4 h. Mordenite (MOR) and Co, Ni and Pd metal supported on the MOR were used as solid catalysts. The catalysts were characterized using X-ray Diffractometer (XRD), Fourier Transform Infrared (FTIR) spectroscopy, and Scanning Electron Microscopy (SEM) to evaluate the physical-chemical properties. Energy Dispersive X-ray (EDX) and Inductively Coupled Plasma (ICP) were used to analyze the amount of metal impregnated on the catalysts. The liquid product was analyzed using Gas Chromatograph-Mass Spectroscopy (GC-MS). Thermal hydrocracking was also conducted at 450 °C with the amount of liquid product was 37.86 wt.%. The highest liquid conversion obtained by mordenite catalyst was 94.66 wt.% at 450 °C and the highest liquid conversion (98.08 wt.%) was reached by Pd/MOR catalyst at 400 °C.